Investigation of the HSPG2 Gene in Tardive Dyskinesia – New Data and Meta-Analysis - Zai, Clement C.; Lee, Frankie H.; Tiwari, Arun K.; Lu, Justin Y.; Luca, Vincenzo de; Maes, Miriam S.; Herbert, Deanna; Shahmirian, Anashe; Cheema, Sheraz Y.; Zai, Gwyneth C.; Atukuri, Anupama; Sherman, Michael; et al. (Frontiers in Pharmacology, 2018)
Tardive dyskinesia (TD) is a movement disorder that may occur after extended use of antipsychotic medications. The etiopathophysiology is unclear; however genetic factors play an important role. The Perlecan (HSPG2) gene was found to be significantly associated with TD in Japanese schizophrenia patients, and this association was subsequently replicated by an independent research group. To add to the evidence for this gene in TD, we conducted a meta-analysis specific to the relationship of HSPG2 rs2445142 with TD occurrence, while also adding our unpublished genotype data. Overall, we found a significant association of the G allele with TD occurrence (p=0.0001); however, much of the effect appeared to originate from the discovery dataset. Nonetheless, most study samples exhibit the same trend of association with TD for the G allele. Our findings encourage further genetic and molecular studies of HSPG2 in TD.